1532. Increased Risk of Bacterial, Fungal and Other Viral Infections During CMV Infection: Decreased Cytokine Production in Response to Toll-Like Receptor Ligands. (26th November 2018) - L'Huillier, Arnaud G; Kumar, Deepali; Bahinskaya, Ilona; Ferreira, Victor H; Humar, Atul
Abstract: Background: In the solid-organ transplant (SOT) setting, CMV is an immunomodulatory virus that indirectly increases the risk for bacterial, fungal and viral infections. However, the pathogenesis of this phenomenon is poorly understood. The aim of our study was to determine whether inflammatory responses to different Toll-like receptor ligands are blunted during CMV infection in SOT patients. Methods: CMV D+/R− SOT patients had blood drawn at the end of CMV prophylaxis and then weekly after onset of CMV viremia. PBMCs were extracted and incubated for 24 hours in the presence of bacterial (LPS), fungal (Zymosan [ZYM]), and viral (Resiquimod [R848]) ligands. Proinflammatory (IL1β), Th1 (IFNγ), Th2 (IL4), immunoregulatory (IL10), and chemotactic (MCP1) cytokines were measured in the supernatant by multiplex ELISA. Results: Thirty-eight SOT patients were followed for at least 9 months. Patients who developed subsequent CMV infection had lower cytokines in response to bacterial, fungal and viral ligands (LPS, ZYM, and R848) at the end of prophylaxis compared with those with no CMV infection. These results were independent of immunosuppression and peripheral blood cell counts. Specifically, these trends were significantly different with respect to IFNγ, IL1β, and IL10 production in response to LPS ( P = 0.003, 0.003, and 0.039, respectively), R848 ( P < 0.001, 0.039, and < 0.001, respectively) and ZYM ( P = 0.039, 0.003, and 0.003, respectively), as well as for MCP1 in response to R848 or ZYM ( P = 0.039 for both). In the cohort with CMV infection, cytokine responses to TLR ligands were even lower during the acute CMV infection when compared with the end of prophylaxis, although this was significant only for IL10 production after R848 stimulation ( P = 0.034). There was no influence of CMV viral load or duration of viremia on cytokine levels. Conclusion: Response to non-CMV antigens during CMV infection was blunted supporting the clinical observation in transplant recipients that CMV infection increases susceptibility to bacterial, fungal, and other viral infections. However, inherent differences in patients that are neither directly related to CMV nor to their net level of immunosuppression also contribute to this increased susceptibility, as cytokine levels at the end of prophylaxis were lower among patients with compared with those without subsequent CMV infection. Disclosures: All authors: No reported disclosures.